Données ethnozoologiques sur l’utilisation des oiseaux dans la médecine traditionnelle chez le peuple Gouro de la Marahoué de Côte d’Ivoire (Afrique de l’Ouest) - Tih Mathieu Koue Bi; K.H Yaokokoré-Beibro; Benoît Kouadio Kasse; Philippe Kouassi Kouassi (VertigO)
An inventory of the birds used in the traditional pharmacopeia of the Gouro people of Côte d’Ivoire was carried out in 19 villages of the area of Marahoué, in the western center of the country, during five months, from august 2010 to december 2010 and 15 months, from february 2012 to april 2013. This study based on the investigations near the local populations identified 44 species of birds used in traditional medicine on the 238 species recognized by these people. This list includes Bycanistes cylindricus which has the status of near threatened bird on the IUCN red list. Out of 17 treatments and desired effects that require the use of birds among the Gouro people, four of them (23.53 % of treatments) are those which claim the most species of birds. Accipitridae and Musophagidae are the most used in zootherapy by this people.